P80 Does self-rated health measure the same concept across countries? insights from a comparison of older adults in england and japan. (2nd September 2017) - Williams, BD; Chandola, T; Cable, N
Abstract : Background: Self-Rated Health (SRH) is predictive of morbidity and mortality, correlates well with objective measurements of physical function and is simple to use in multidisciplinary surveys. It could be a useful way of comparing health policies in different countries. However, it may not be comparable between countries which may wish to contrast health policies, for example Britain and Japan, because of linguistic, cultural or health differences. We aimed to test for differences in the association between SRH and physical function (grip strength), mental health (depression) and cardiovascular risk (smoking and BMI) between older adults in Japan and England. Methods: Data were used from the English Longitudinal Study of Ageing (ELSA; 2004, 2008 and 2012) and the Japanese Study of Ageing and Retirement (JSTAR; 2007, 2009 and 2011), giving n=10, 174 ELSA participants and n=4279 JSTAR participants, all aged 50 and above. Multilevel binary logistic regression was used to test whether participants' country of residence was associated with odds of fair or poor SRH and whether the country of residence would moderate associations between SRH and grip strength, depression, smoking or BMI. Results: Japanese women (15.6%) and men (14.1%) were less likely to report fair/poor SRH than English women (23.6%) and men (24.1%). After adjusting for covariates these differences remained for men (Odds Ratio [OR] for Japanese men 0.64, 95% CI 0.74–0.85) but not for women (OR for Japanese women 1.02, 95% CI 0.47–1.34). Grip strength (OR's women 0.86–0.89; men 0.91–0.94), depression (OR's women 4.40–6.82; men 5.25–9.26), BMI (OR's women 1.11–1.16; men 1.10–1.15) and smoking status (OR's≥20 cigarettes per day women 3.07–7.22; men 2.13–4.54) were associated with fair/poor SRH. No interactions were found between country and grip strength (OR's women 0.95–1.03; men 0.99–1.05) or depression (OR's women 0.63–1.39; men 0.50–1.22) but were found for BMI (OR's women 0.89–0.98; men 0.87–0.97) and smoking (OR's≥20 cigarettes per day women 0.12–0.34; men 0.20–0.55). The interaction between country and BMI reduced when the analysis was restricted to those with a BMI less than 30 (OR's women 0.93–1.07; men 0.90–1.05). Conclusion: Our findings agree with previous research that SRH captures general physical and mental health similarly across countries. We may need more caution comparing SRH across countries when considering other aspects of health. We find that cardiovascular risk has different associations with SRH in England and Japan, possibly reflecting differences in cultural norms and different stages in their obesity and tobacco epidemics.